2015
DOI: 10.1159/000439219
|View full text |Cite
|
Sign up to set email alerts
|

Remote Ischemic Preconditioning May Attenuate Renal Ischemia-Reperfusion Injury in a Porcine Model of Supraceliac Aortic Cross-Clamping

Abstract: Aim: The effect of remote ischemic preconditioning (RIPC) in decreasing renal ischemia-reperfusion injury (IRI) during a suprarenal aortic cross-clamping was examined in a swine model. Materials and Methods: Four groups of pigs were examined: (a) ischemia-reperfusion (IR) group, renal IRI produced by 30 min of supraceliac aortic cross-clamping; (b) RIPC I group, the same renal IRI following RIPC by brief occlusion of the infrarenal aorta (15 min ischemia and 15 min reperfusion); (c) RIPC II group, the same ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Other scholars, such as Chao CS, found that when the occlusion time of the zone II abdominal aorta in pigs exceeded 30 minutes with a balloon catheter, the intra-abdominal pressure increased, pathological changes in multiple organs occurred, and the mixed venous oxygen saturation was reduced (15). Athanasiadis D et al concluded that Scr levels increased 30 min after abdominal aorta occlusion above the celiac trunk in pigs with open aneurysms (16).…”
Section: Discussionmentioning
confidence: 99%
“…Other scholars, such as Chao CS, found that when the occlusion time of the zone II abdominal aorta in pigs exceeded 30 minutes with a balloon catheter, the intra-abdominal pressure increased, pathological changes in multiple organs occurred, and the mixed venous oxygen saturation was reduced (15). Athanasiadis D et al concluded that Scr levels increased 30 min after abdominal aorta occlusion above the celiac trunk in pigs with open aneurysms (16).…”
Section: Discussionmentioning
confidence: 99%
“…Other scholars, such as Chao CS, found that when the occlusion time of the zone II abdominal aorta in pigs exceeded 30 minutes with a balloon catheter, the intra-abdominal pressure increased, pathological changes in multiple organs occurred, and the mixed venous oxygen saturation was reduced [11] . Athanasiadis D et al concluded that Scr levels increased 30 min after abdominal aorta occlusion above the celiac trunk in pigs with open aneurysms [12] .…”
Section: Discussionmentioning
confidence: 99%
“…In regard to sevoflurane, we have not identified any renal rIC studies using this agent. In contrast, the related agent isoflurane is widely used both in small and large animal studies, where renoprotective effects of rIC is reported in some [ 23 , 29 32 ] but not all [ 16 , 20 ]. Sevoflurane in combination with buprenorphine was chosen since they provide optimal anaesthetic and analgesic effects in combination with a safe profile when compared with i.v.…”
Section: Discussionmentioning
confidence: 99%